Growth, yield and quality of poblano chili pepper grown in hydroponics under greenhouse - Hernández Hernández, Brenda Nataly; Tornero Campante, Mario Alberto; Sandoval Castro, Engelberto; Rodríguez Mendoza, María de las Nieves; Taboada Gaytán, Oswaldo Rey; Peña Olvera, Benjamín Valeriano (Revista Mexicana de Ciencias Agrícolas, 2021)
The poblano chili pepper crop sown in soil in the Alto Atoyac in Puebla has been affected by the presence of diseases caused by fungi, bacteria and nematodes, generating losses in yield and reduction of the sowing area. The production under greenhouse and hydroponics is an alternative solution to this problem, since it allows the development of crops in a controlled environment using inert substrates, ensuring a greater percentage of production. The objective was to evaluate the growth, yield and fruit quality of two local varieties of poblano chili pepper (Tlacotepec and Tlalancaleca) and a commercial variety (San Luis), supplied nutritionally by three concentrations of the Steiner nutrient solution under greenhouse and hydroponics in order to know their agronomic and productive behavior. A 3x3 factorial treatment design in a completely randomized experimental design was considered. The variables evaluated were: plant height, stem thickness, number of leaves, number of bifurcations, number of flowers, yield and fruit quality. The results showed that the San Luis variety reached the highest yield and fruit quality. As for the three concentrations of nutrient solution, there was no significant effect on the yield and the agronomic behavior of creole varieties in the substrate, greenhouse and hydroponics system may be an option for the production of poblano chili pepper in the Alto Atoyac region.
Keywords: Capsicum annuum L.; protected agriculture; nutrient solution